Fenomena Penggunaan Tanda Baca dalam Artikel Bahasa Arab pada Website BBC News Onine - Siti Ghitsna Naily Nasyithoh; Al Fahrur Rozi; Syamsul Anam (Alfaz (Arabic Literatures for Academic Zealots), 2021)
The purpose of this study is to describe language errors in the use of punctuation marks. This qualitative descriptive research method is used by the author to examine the phenomenon of punctuation in Arabic articles on the BBC News Online website. The results of the study indicate that language errors in the BBC News Online news text are errors from the punctuation aspect which consist of errors in the use of colons (:), the use of quotation marks (“...”), the use of commas (, ( and Separate (-) Errors in writing BBC News Online are due to the editor's lack of caution in writing and lack of understanding of the use of punctuation. There are not many errors in the news, only a few, even in the content of this online news on BBC News Online. almost everything right.